Student Characteristics in the Eyes of Teachers: Differences Between Novice and Expert Teachers in Judgment Accuracy, Observed Behavioral Cues, and Gaze - Seidel, Tina; Schnitzler, Katharina; Kosel, Christian; Stürmer, Kathleen; Holzberger, Doris (Educational psychology review, 2021)
The present study investigates teacher diagnostic skills when observing student engagement and inferring to underlying student characteristic profiles. Five student profiles as empirically determined in previous studies are selected: three incoherent (overestimating, uninterested, and underestimating) and two coherent (strong and struggling) profiles. Teacher professional vision and underlying assumptions about processes of noticing and reasoning about the chosen diagnostic situation serve as a conceptual basis. In the empirical study (N = 41 participants), it is investigated to what extent expert and novice teachers differ with regard to judgment accuracy of underlying student profiles, observed student cues used for judgment, and teacher gaze as perceptual indicator. The study task involved observing a video clip and diagnosing five marked students based on their underlying profiles. First, findings of the study suggest that expert teachers are more accurate in judging incoherent profiles compared to novices. Second, both novices as well as experts state valid behavioral cues when inferring from student engagement to underlying student profile. Third, experts spend more teacher gaze on student profiles which might need adaptive pedagogical action (struggling, underestimating, uninterested student). The study provides first evidence on teacher gaze during the professional task of diagnosing individual students in the process of teaching. Regarding the conceptual model of teacher professional vision teacher gaze can serve as an additional operationalization of the noticing component of teacher professional vision.